2019
DOI: 10.1021/acs.biochem.9b00742
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Rescue and Glycosidic Conformational Analysis of the Twister Ribozyme

Abstract: The number of self-cleaving ribozymes has increased sharply in recent years, giving rise to elaborations of the four known ribozyme catalytic strategies, α, β, γ, and δ. One such extension is utilized by the twister ribozyme, which is hypothesized to conduct δ, or general acid catalysis, via N3 of the syn adenine +1 nucleobase indirectly via buffer catalysis at biological pH and directly at lower pH. Herein, we test the δ catalysis role of A1 via chemical rescue and the catalytic relevance of the syn orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Cluster analyses further raise concerns about the possible over-representation of syn orientations in RNA DNMPs, especially in the RNA AA DNMP for both force fields, even though experimental results concluded that Δ G syn → anti = −1.2 kcal/mol for adenosine residues at 35 °C. , There is mounting evidence for the importance of the syn orientation, especially in the catalytic activity of ribozymes and higher-order RNA structures, where adenosine residues adopt energetically unfavorable syn orientations. Nevertheless, color-coded cluster analyses show that RNA AA exhibits the greatest number of structures in syn orientations, especially when using the ff99OL3 force field, which raises the question of whether the χ torsional parameters should be fine-tuned for adenosine residues.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster analyses further raise concerns about the possible over-representation of syn orientations in RNA DNMPs, especially in the RNA AA DNMP for both force fields, even though experimental results concluded that Δ G syn → anti = −1.2 kcal/mol for adenosine residues at 35 °C. , There is mounting evidence for the importance of the syn orientation, especially in the catalytic activity of ribozymes and higher-order RNA structures, where adenosine residues adopt energetically unfavorable syn orientations. Nevertheless, color-coded cluster analyses show that RNA AA exhibits the greatest number of structures in syn orientations, especially when using the ff99OL3 force field, which raises the question of whether the χ torsional parameters should be fine-tuned for adenosine residues.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that a similar mechanism is operative in the hairpin ribozyme, enabling the O2′ to relinquish its proton to a suitable general base (i.e., one with a pK a near neutrality so that it is in its deprotonated form in the reactant state) or to buffer or water during the course of the reaction. 5,13,67,68 Until now, we have considered the O2′-to-pro-S P NPO hydrogen bond as an inhibitory interaction since it likely raises the pK a of the nucleophile. However, if the pro-S P NPO functions as the catalytic general base, the high frequency of hydrogen bond formation would actually favor catalysis.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Quantum mechanical/molecular mechanical (QM/MM) MD simulations were also performed for the glmS ribozyme with the general base (G40) in its deprotonated functional form, which indicated that the O2′ is deprotonated by G40 during nucleophilic attack, when in the course of the reaction the p K a of the O2′ would be lower. We propose that a similar mechanism is operative in the hairpin ribozyme, enabling the O2′ to relinquish its proton to a suitable general base (i.e., one with a p K a near neutrality so that it is in its deprotonated form in the reactant state) or to buffer or water during the course of the reaction. ,,, …”
Section: Discussionmentioning
confidence: 98%
“…20,69 Such catalysis has also been shown to rescue ribozymes that would otherwise be inactive. 69 Furthermore, experiments performed in media containing the 15 most abundant metabolites of E. coli, which comprise 80% of the E. coli metabolome, demonstrated a decrease in thermodynamic stability and an increase in chemical stability (i.e., resistance to degradation) for a series of structured RNAs (the guanine aptamer, the CPEB3 ribozyme, and tRNA Phe ) of ∼2to ∼10fold relative to standard in vitro conditions, such as 2 and 25 mM free Mg 2+ . 70 Such changes could favor conformations other than P zym for the Osa 1−3 and Osa 1−8 ribozymes.…”
Section: ■ Discussionmentioning
confidence: 99%